2011
DOI: 10.1007/s00268-011-1354-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Brain Natriuretic Peptide (BNP) Is a Better Predictor of Adverse Cardiac Events Compared to Preoperative Scoring System in Patients Who Underwent Abdominal Surgery

Abstract: We have demonstrated that elevated preoperative BNP levels are independent predictors of adverse cardiac events in a cohort of patients undergoing major abdominal surgery in a general surgery department, and this is the first study about this specific cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…In total, 24 of the 28 studies 29,[34][35][36][37][38][40][41][42][43][46][47][48][49][50][51][52][53][55][56][57][58][59][60] were prospective observational cohort studies. Of the remaining four studies: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 24 of the 28 studies 29,[34][35][36][37][38][40][41][42][43][46][47][48][49][50][51][52][53][55][56][57][58][59][60] were prospective observational cohort studies. Of the remaining four studies: …”
Section: Methodsmentioning
confidence: 99%
“…Of the remaining studies, three reported exclusively on patients undergoing emergency surgery, 38,45,48 and one documented both elective and emergency surgeries that were classified as being high risk. 46 Certain studies investigated outcomes in a specific surgical discipline, including thoracic surgery (4), 36,50,51,54 vascular (7), 29,40,42,44,55,57,59 orthopaedic (5), 45,[47][48][49]60 major abdominal (1), 56 oesophagectomy (1), 41 while the rest documented outcomes following a variety of surgeries performed (10), 34,35,[37][38][39]43,46,52,53,58 including a mix of general, head and neck, gynaecological, orthopaedic, vascular, urological, neurosurgery and thoracic surgery.…”
Section: Included Studiesmentioning
confidence: 99%
“…Most of the studies evaluating BNPs had levels drawn within 2 weeks prior to the day of surgery, typically at one time-point, however recent studies have incorporated perioperative BNP levels (levels drawn preoperatively and up to 5 days following surgery) [36,38,43,[45][46]. Preoperative BNPs have been found to be an independent predictor or associated with increased postoperative cardiac events [35][36][37][38][39][40][41][42][43][44]47,142] or mortality [24,41,[46][47] in noncardiac surgery, including cardiac morbidity at 30 days following discharge from hospitalization [38].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 99%
“…Studies measuring BNPs in patients undergoing noncardiac surgery have investigated the role in the perioperative period for risk prediction or associations with adverse postoperative myocardial events [35][36][37][38][39][40][41][42][43][44], prolonged hospital stay [45] and mortality [24,[46][47] (see Table 4). Most of the studies evaluating BNPs had levels drawn within 2 weeks prior to the day of surgery, typically at one time-point, however recent studies have incorporated perioperative BNP levels (levels drawn preoperatively and up to 5 days following surgery) [36,38,43,[45][46].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 99%
“…Recent advancements in the diagnosis of CRC and the worldwide diffusion of screening programs have led to an increase in the detection of pathologically T1 (pT1) CRCs [4,5]. The increasing of early stage CRCs allowed, in the last decades, the development of less invasive treatment including local resections, such as endoscopic mucosal/submucosal dissection (ESD) and transanal endoscopic microsurgery (TEM) in selected rectal cancer patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%